DEVELOPING EDUCATIONAL E-POSTER BASED ON INSTAGRAM FOR THE TOPIC OF CORROSION AFFECTING FACTORS - Rahma Mardiana; Ratu Fazlia Inda Rahmayani; Muhammad Nazar; Sarlivanti Sarlivanti (Chimica Didactica Acta, 2023)
The development of more sophisticated technology has become a powerful tool for achieving more effective and efficient educational objectives. In this instance, learning media that employ social media has been extensively adopted, and one of the potential alternatives is to utilize social media as learning media. This study aims to develop an e-poster social media Instagram on the material factors that affect corrosion and see the response of Chemical Education students of FKIP USK to the developed media. Using the ADDIE approach, RD (Research and Development) is the sort of research used. Student requirements surveys, an evaluation of the viability of the e-poster medium, and student response questionnaires were used to gather data. This research was carried out on the campus of the Faculty of Teacher Training and Education, Syiah Kuala University, Department of Chemistry Education, with research subjects being students majoring in Chemistry Education Force 2020 FKIP Syiah Kuala University consists of 3 class units with a total of 61 students consisting of 57 female and four male. The results showed that With an average percentage of 89 percent, the generated e-poster learning material meets the requirements for "very viable." With an average score of 84 percent, student reactions to the generated medium met the criterion for "extremely feasible." Based on the study's findings, the e-poster is a viable alternative learning medium.Keywords: Development; Learning Media; Instagram; E-Poster; Corrosion